CULTURAL LIFE IN CHINA UNDER THE HAN EMPIRE. (Universal International Scientific Journal, 2026)
This article analyzes the cultural life of China during the Han Dynasty (206 BCE – 220 CE), a key period in the formation of Chinese civilization. It examines the main areas of cultural development, including philosophy, the educational system, literature, art, science, and religious beliefs. Particular attention is paid to the role of Confucianism, which was enshrined as the official state ideology during the Han Dynasty and exerted a significant influence on the political, social, and cultural life of society. The article highlights the activities of state academies, the development of the examination system, and the spread of written culture, which contributed to the formation of an educated bureaucracy. Achievements in historiography are analyzed, primarily the creation of fundamental historical works that laid the foundations of the Chinese historical tradition. Advances in science and technology, including astronomy, medicine, mathematics, and the invention of paper, which played a significant role in the development of culture and the transmission of knowledge, are also considered. A special place is given to the study of fine arts, architecture, and funerary rites as reflections of the era's worldview and spiritual values. The conclusion is that the cultural legacy of the Han Empire had a lasting influence on the subsequent development of Chinese culture and statehood.
Keywords: Han Dynasty, cultural life, Confucianism, Chinese civilization, philosophy, education, historiography, science and technology, invention of paper, art, architecture, spiritual values.